Голубой журавль: повесть / М. Н. Казакова ; худож. Г. Акулов - Казакова Мария Никитична (Детская литература, 1989)
Экземпляры: аб. ДБ (2017.20.12) / Инвентарный номер: 3887 / Авт.знак: К14 / ББК: 84(2Рос)